Pertambahan Berat Badan Akseptor KB Suntik 3 Bulan Di Puskesmas Danurejan 1 Yogyakarta - Nuraini; Wiwin Hindriyawati; Sumirah (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2023)
Background: Family planning is a program to help improve public health by regulating pregnancy. Injections are contraception with high interest as well as being effective and efficient in preventing pregnancy. injecting contraceptive users in the special region of Yogyakarta in 2021 are included in the top 3 enthusiasts of contraceptive users consisting of 5,317 injections, 7,741 IUDs, 6,354 condoms, with 33,702 fertile couples. Injectable contraception has the side effect of increasing body weight for women as acceptors, even so, there are still many enthusiasts who use injectable contraception. Objetive: The aim is to determine the weight gain of 3-month injectable contraceptive acceptors. Methode: This research is descriptive research. The sample in this study were 259 respondents with technical accidental sampling. Result: The results showed that 159 respondents (61.4%) experienced normal weight gain in the first year of 2.9 kg, and 42 respondents (16.2%) gained more than 2.9 kg of body weight, normal weight gain in the second year 5.9 kg in 44 respondents (17%), and overweight in the second year > 5.9 kg in 14 respondents (5.4%). With weight gain in the normal category and more emphasis on midwives or health workers to be able to provide adequate counseling regarding weight gain for mothers who use 3-month injection contraception.